Determining the Phosphorus Release Curve for Smizyme TS G5 2,500 Phytase in Nursery Pigs - M. R. Wensley; J. C. Woodworth; J. M. DeRouchey; S. S. Dritz; M. D. Tokach; R. D. Goodband; H. I. Calderón; J. M. Faser; B. L. Guo (Kansas Agricultural Experiment Station Research Reports, 2020)
A total of 280 nursery pigs (DNA 241 × 600, initially 22.8 lb) were used in a 21-d growth trial to determine the available P (aP) release curve for Smizyme TS G5 2,500 (Origination, LLC., Maplewood, MN). Pigs were weaned at approximately 21 d of age, randomly allotted to pens based on initial body weight (BW), and fed common starter diets. On d 21 post-weaning, considered d 0 of the study, pens were blocked by BW and randomly allotted to 1 of 7 dietary treatments with 5 pigs per pen and 8 pens per treatment. Seven 1-ton batches of basal diet were manufactured and subsequently divided to be the major portion of experimental diets. Dietary treatments were formulated to include increasing aP derived from either an inorganic P source (0.11%, 0.19%, or 0.27% from monocalcium P) or increasing phytase (250, 500, 1,000, or 1,500 FTU/ kg). Diets were corn-soybean meal-based and contained 1.24% standardized ileal digestible (SID) lysine with other amino acids set to meet or exceed NRC5 requirement estimates. Prior to beginning the 21-d study, all pigs were fed the negative control diet containing 0.11% aP for a 3-d period (d 18 to 21 post-weaning). Diets containing phytase were submitted for complete phytase analysis (Eurofins Scientific Inc., Des Moines, IA) using the AOAC official method 2000.12,6 and analyzed concentrations were 265, 470, 1,000, or 1,450 FTU/kg. On d 21 of the experiment, the pig closest to the mean BW in each pen was euthanized and the right and left fibula were collected to determine bone ash with one fibula defatted and the other not prior to ashing. Overall (d 0 to 21), pigs fed increasing aP from inorganic P had improved (linear,P<0.01) performance across all response criteria measured. When using both the defatted and non-defatted bone mineral procedures, pigs fed increasing aP from inorganic P had increased (linear,P<0.01) bone ash weights and percentage bone ash. Pigs fed increasing phytase had increased (linear,P<0.01) bone ash weights and percentage bone ash (linear and quadratic,P<0.05). The aP release increased (linear,P<0.01) up to the highest phytase dose when using gain-to-feed ratio (G:F), bone ash weight, or defatted percentage bone ash as indicators of release. When using average daily gain and non-defatted percentage bone ash, aP release increased in a linear and quadratic fashion (P<0.01). In conclusion, the magnitude of aP release curves depends on the response criteria measured, but Smizyme TS G5 2,500 appears to have a similar aP release to other commercially available phytase sources. When combining the release values for defatted bones in this experiment with a previous experiment,7 the aP release equations for Smizyme TS G5 2,500 are: aP = (0.197 × FTU) ÷ (584.956 + FTU), aP = (0.175 × FTU) ÷ (248.348 + FTU), and aP = (0.165 × FTU) ÷ (178.146 + FTU) for ADG, G:F, and percentage bone ash, respectively.
Keywords: phosphorus; phytase; pig; release value